Does Regional Traffic Management Center police have a good quality of work-life?: A qualitative study - Wijaya, Yunus Adi; Andriana, Kiki Rizki Fista; Hariyanti, Tita; Dewi, Komang Ayu Krisna (PT Saintek Medika Nusantara, 2022)
Working as a police officer at the Regional Traffic Management Center (RTMC) demanded physical, psychological, mental, emotional, and physical abilities. These demands often create pressure and reduce their quality of life and performance. This study aims to determine the quality of work-life (QWL) of the RTMC police officer. This research used the qualitative method of hermeneutic interpretive phenomenology. The data required for the study was collected through semi-structured interviews held with 4 participants selected according to purposive sampling with criteria: (1) 20-40 years old; (2) Members of the police who served in the Regional Police Traffic Management Center at the time of carrying out their work; (3) Members of the police who have experienced work stress and continued until data saturation was reached. Based on the results of the data analysis, the researchers obtained two main themes, including 1) Stress in working as RTMC police officers; and 2) Coping mechanisms to overcome the work stress of the RTMC police officers. The good QWL of police officers will encourage work performance, including the emergence of discipline, a sense of responsibility, and compliance. Leaders can provide motivation, trust and establish rational regulations to prevent the increasing stress of the work of the police officers.